The Janus Head Article - On Quality in the Documentation Process - Andersen, Henrik; Christoffersen, Ellen (Language at Work - Bridging Theory and Practice, 2006)
The god Janus in Greek mythology was a two-faced god; each face had its own view of the world. Our idea behind the Janus Head article is to give you two different and maybe even contradicting views on a certain topic. In this issue the topic is quality in the documentation process. In the first half of this issue’s Janus Head Article translators from the international company Grundfos give us their view of quality and how quality is managed in the documentation process at Grundfos. In the second half of the Janus Head Article scholars from the University of Southern Denmark describe and discuss quality in the documentation process at Grundfos from a researcher’s point of view.